2017
DOI: 10.5219/730
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties, total phenolic and total flavonoid content of the Slovak white wines - welschriesling and chardonnay

Abstract: The biologically active compounds in wines, especially phenolics, are responsible for reduced risk of developing chronic diseses (cardiovascular diseases, cancer, diabetes, Alzheimer disease, etc.), due to their antioxidant activities. Twenty six Slovak white wines, produced from different geographical origins, were examined in this study. The antioxidant activity, total phenolic and flavonoid contents of two types monovarietal wines -Welschriesling and Chardonnay were evaluated. All three mentioned parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…In comparison with the chardonnay wines from Montenegro (TPC 226 mg GAE L −1 ) [47], the content in Slovak chardonnay wines was higher in more than 100 mg GAE L −1 . Our results are also in agreement with experiments by Bajčan et al [30] and Čéryová et al [31], who examined the antioxidant activity, total phenolic and flavonoid contents in monovarietal wines of Welschriesling, chardonnay. According to their results, Slovak white wines were high in polyphenols (average content was 303.2 mg GAE.L−1 in Welschriesling, resp.…”
Section: Influence Of Varietysupporting
confidence: 93%
See 2 more Smart Citations
“…In comparison with the chardonnay wines from Montenegro (TPC 226 mg GAE L −1 ) [47], the content in Slovak chardonnay wines was higher in more than 100 mg GAE L −1 . Our results are also in agreement with experiments by Bajčan et al [30] and Čéryová et al [31], who examined the antioxidant activity, total phenolic and flavonoid contents in monovarietal wines of Welschriesling, chardonnay. According to their results, Slovak white wines were high in polyphenols (average content was 303.2 mg GAE.L−1 in Welschriesling, resp.…”
Section: Influence Of Varietysupporting
confidence: 93%
“…In our study, all wines presented relatively high values for the antioxidant activity, ranged between 51.06 and 72.53% of inhibition of DPPH (average: 63.30% for chardonnay, 58.62% for pinot blanc and 64.45 for pinot gris wines). Our results for antioxidant activity were correlated with previously published data for white wines [30,31,48]. According to several studies, polyphenolic compounds have shown a different behaviour towards DPPH free radical, both in terms of capacity and rate of scavenging [49,50].…”
Section: Influence Of Varietysupporting
confidence: 90%
See 1 more Smart Citation
“…Many of these compounds have been reported to have multiple biological activities, including cardioprotective, anti-carcinogenic, antiviral, antidegenerative and antibacterial properties (Bystrická et al, 2014;King et al, 2006;Santos-Buelga and Scalbert, 2000). In previous studies, we described some antioxidant properties, such as total polyphenol content, total flavonoid content, total anthocyanin content and antioxidant activity of the Slovak monovarietal red (Bajčan et al, 2012a,b; and white (Bajčan et al, 2017) wines originating in different vineyard areas, excluding Tokaj wine region. Tokaj wine region lies in the Lower Zemplín in the south-eastern corner of Slovakia.…”
Section: Introductionmentioning
confidence: 97%